Schistosomes in the north: a unique finding from a prosobranch snail using molecular tools - Aldhoun, Jitka Asma; Faltýnková, Anna; Karvonen, Anssi; Horák, Petr (Parasitology international, 2009)
Samples of schistosome cercariae from three different snail species (Lymnaea stagnalis, Radix auricularia and Valvata (Tropidina) macrostoma) collected from lakes in Central Finland were analyzed using molecular techniques. Based on sequences of ITS region of rDNA, the parasite isolates from L. stagnalis and R. auricularia belong to Trichobilharzia szidati and T. franki, respectively. This confirms a wide distribution of these two species in Europe. On the other hand, the isolates from V. macrostoma represent a unique finding--they belong to yet unknown schistosome species falling into the bird schistosome clade. Therefore, identification of natural final hosts and morphological characterization of particular developmental stages need to be performed in the future.
Keywords: Molecular Sequence Data; sekvenční analýza DNA; DNA, Ribosomal Spacer; Sequence Analysis, DNA; Snails; molekulární sekvence - údaje; zvířata; Lymnaea; DNA, Helminth; Schistosomatidae; DNA helmintů; fylogeneze; Phylogeny; mezerníky ribozomální DNA; hlemýždi; Animals